Pemanfaatan Artificial Intelegence untuk Membangun Website Pembelajaran bagi Guru dan Dosen pada Perkumpulan Profesi Multimedia dan Teknologi Informasi (PPMULTINDO) - Cahaya Jatmoko; Sindhu Rakasiwi; Feri Agustina; Daurat Sinaga; Heru Lestiawan (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The utilization of Artificial Intelligence (AI) technology in education has become increasingly important with the development of information technology. This research aims to provide training for teachers and lecturers in using AI to build interactive and effective learning websites. The method used is online training via Zoom Meeting, which includes an introduction to basic AI concepts, practice creating learning websites, and evaluating training outcomes. The training was conducted over three days from October 26 to 28, 2024, with participants from various regions across Indonesia. The results showed that participants were able to understand AI concepts and apply them effectively in building learning websites more efficiently and creatively. Additionally, the use of AI helped improve the quality of learning content to be more personalized and adaptive to students' needs. Thus, the application of AI in education can serve as an innovative solution to enhance the quality of learning in the digital era.